Kemampuan Toilet Training Memiliki Hubungan dalam Pemakaian Diapers pada Anak Usia Toddler - Helena Golang Nuhan; I Nyoman Ribek (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2021)
Background : Teaching toilet training to children is not easy to do because it requires physical, psychological, and cognitive preparation in children. The failure of toilet training can be caused by several things, namely lack of knowledge, use of diapers, the occurrence of sibling blues, and others. This study aims to determine the relationship between the use of diapers on the ability of toilet training in toddler age children. Methods: The method used is a descriptive method with a cross sectional approach that uses purposive techniques. Where the sample in this study is parents who have children aged 12-36 months, which was carried out at the Children's Clinic of Budhi Asih Hospital with a total sample of 106 respondents. Data were analyzed using chi-square analysis technique Results: The research that has been carried out by researchers shows that from 106 respondents, 38 (55.9%) using diapers in low intensity ( 16) succeeded in training children in toilet training and as many as 30 (78.9%) using diapers in high intensity (16). The P value = 0.030 and the OR value = 2.961 (95% CI = 1.186-7.329) it can be concluded that there is a relationship between the use of diapers and the ability of toilet training. Conclusion: the results of the above study indicate that most parents still choose to use diapers in the care of their children. Therefore, it is hoped that parents will care more and pay more attention to their children in aspects of child development, one of which is the ability to toilet training.